Contribution of graph theory to the understanding of social dynamics - Gamboa, Alfredo Javier Pérez (AWARI, 2023)
This review article examines how graph theory has contributed significantly to understanding social dynamics by discussing its applicability to social network analysis. A predominantly qualitative study was carried out, with a scoping review design aimed at understanding how this set of tools facilitates studying human interactions and the structure of social groups. The main results highlighted key concepts such as centrality, clusters, connectivity, and network resilience, as well as their applications to analyzing social phenomena such as information diffusion, opinion formation, disease spread, and social cohesion. In addition, the methodological challenges and limitations of graph theory were examined, to propose future directions for interdisciplinary research that delve into the interaction between mathematics and social sciences, especially Social Psychology applied to collective behavior and the social network analysis.